Thanaka (Limonia acidissima) and deet (di-methyl benzamide) mixture as a mosquito repellent for use by Karen women - S. W. Lindsay (2018)
The prevention and treatment of drug-resistant malaria is becoming increasingly difficult. On the Thai-Myanmar border multi-drag resistant strains of falciparum malaria are increasing and, because the malaria vector Anopheles bite outdoors during early evening, insecticide house-spraying or impregnated bednets provide only limited protection. Therefore, the protective efficacy of repellent formulations containing di-methyl benzamide (deet) and permethrin against local vectors was estimated, when applied to the skin, and their acceptability amongst pregnant Karen women who are at relatively high risk from malaria was assessed. Human landing catches of mosquitoes showed that almost complete protection was achieved using different formulations of 20% deet and 0.5% permethrin for up to 6 h. All-night collections from human subjects indicated that this repellent combination reduced exposure to malaria parasites by at least 65 and 85% for those transmitted by Anopheles minimus and An. maculatus, respectively, the two principal vectors in this area. Pregnant women in the camps preferred repellents which were mixed with 'thanaka', a root paste made from pulp of the wood apple tree, Limonia acidissima, used locally as a cosmetic. Apart from a temporary warming sensation where repellent thanaka was applied to the skin, the repellents were well tolerated. An intervention trial is currently in progress to determine whether deet mixed with thanaka can protect pregnant women against malaria in this part of the world. Bioassays using a laboratory strain of Aedes aegypti demonstrated that thanaka is itself slightly repellent at high dosages and the mixture with deet provides protection for over 10 h. This treatment would therefore also provide some personal protection against dengue, which is increasing locally, transmitted by Ae. aegypti and Ae. albopictus biting during the daytime.